2013
DOI: 10.1136/bcr-2012-008388
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer with metastases to the kidney: a rare manifestation of a common disease

Abstract: A 66-year-old Caucasian man with a background of prostate cancer presented with a progressive history of nausea, reduced appetite, shortness of breath and a distended abdomen. Radiological imaging revealed a left-sided renal mass and gross ascites suggestive of metastatic renal cell carcinoma (RCC). Subsequent histological examination and immunostaining of renal mass biopsy revealed features characteristic of metastatic moderately differentiated to a focally poorly differentiated, large duct type of prostatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…It has been assumed that metastatic infiltration presumably results from arterial tumor embolization since kidney has a highly vascular structure. [5] Interestingly, as far as we know in the literature renal metastasis from PCa always occurs at the left side. The underlying hematogenous or lymphogenous spread mechanisms are unknown therefore; further studies are needed in this issue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been assumed that metastatic infiltration presumably results from arterial tumor embolization since kidney has a highly vascular structure. [5] Interestingly, as far as we know in the literature renal metastasis from PCa always occurs at the left side. The underlying hematogenous or lymphogenous spread mechanisms are unknown therefore; further studies are needed in this issue.…”
Section: Discussionmentioning
confidence: 99%
“…In the report by Khan et al [5] , prostate adenocarcinoma and leftsided renal mass (5.5 cm in size) compatible to renal cell carcinoma with extra-renal extension was described in a 66-year-old male patient. Authors considered primary and metastatic renal cell carcinoma, lymphoma and benign lesions including angiomyolipoma or oncocytoma in the initial differential diagnosis but biopsy revealed prostatic origin of the mass lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prostate carcinoma comprises 15% of all men's cancers in developed countries and 4% of men's cancers in developing countries. Typically, prostate cancer metastasizes to the bone, lungs, and liver and locally invades the seminal vesicles, bladder, rectum, and regional lymph nodes (31). However, renal mass lesion should be considered in primary tumor metastasis, especially among the left size localized patients (32).…”
Section: Prostate Cancer and Kidneymentioning
confidence: 99%
“…Literature has shown diverse sites of possible metastases, these atypical metastatic locations being the ocular region, brain, respiratory tract, testes, mammary and parotid glands, the skin and the lymphatic system [4]. Some studies reported that 15% of men with PC might be affected by atypical metastases at diagnosis [5] [6].…”
Section: Introductionmentioning
confidence: 99%